Possibility of Using NO Modulators for Pharmacocorrection of Endothelial Dysfunction After Prenatal Hypoxia - Belenichev, I. F.; Popazova, O. O.; Yadlovskyi, O.; Bukhtiyarova, N. V.; Ryzhenko, V. P.; Pavlov, S. V.; Oksenych, V.; Kamyshnyi, O.; Бєленічев, Ігор Федорович; Попазова, Олена Олександрівна; Бухтіярова, Ніна Вікторівна; Риженко, Віктор Павлович; et al. (My University, 2025)
Abstract: Prenatal hypoxia (PH) is a key factor in the development of long-term cardiovascular disorders, which are caused by various mechanisms of endothelial dysfunction (ED), including those associated with NO deficiency. This emphasizes the potential of therapeutic agents with NO modulator properties, such as Thiotriazoline, Angiolin, Mildronate, and L-arginine, in the treatment of PH. Methods: Pregnant female rats were given a daily intraperitoneal dose of 50 mg/kg of sodium nitrite starting on the 16th day of pregnancy. A control group of pregnant rats received saline instead. The resulting offspring were divided into the following groups: Group 1—intact rats; Group 2—rat pups subjected to prenatal hypoxia (PH) and treated daily with physiological saline; and Groups 3 to 6—rat pups exposed to prenatal hypoxia and treated daily from the 1st to the 30th day after birth. Levels of sEPCR, Tie2 tyrosine kinase, VEGF-B, SOD1/Cu-Zn SOD, GPX4, and GPX1 in the heart’s cytosolic homogenate were assessed using ELISA. The expression of VEGF and VEGF-B mRNA was analyzed via real-time polymerase chain reaction, and the nuclear area of myocardial microvessel endothelial cells was evaluated morphometrically. Results: We have shown that only two representatives of this group—Angiolin and Thiotriazoline—are able to exert full effect on the indices of endothelial dysfunction after PH to decrease sEPCR, increase Tie-2, VEGF-B and VEGF-B mRNA, Cu/ZnSOD, and GPX in myocardial cytosol, and increase the area of endotheliocyte nuclei in 1- and 2-month-old rats in comparison with the control. Conclusions: Our results experimentally substantiate the necessity of early postnatal cardio- and endothelioprotection using NO modulators, taking into account the role of NO-dependent mechanisms in the pathogenesis of cardiovascular system disorders in neonates after PH.
Keywords: prenatal hypoxia; cardioprotective; endothelioprotection; NO system; angiolin; L-arginine; thiotriazoline; Mildronate